PENGARUH QARDH TERHADAP PENCAPAIAN TINGKAT SOLVABILITAS DANA TABARRU’ PADA PERUSAHAAN UNIT ASURANSI JIWA SYARIAH - Nugraha Malik, Muhammad; Nirmalawati, Dyah; Ritha, Henny (JAMBIS : Jurnal Administrasi Bisnis, 2024)
This study aims to analyze the impact of qardh on solvency levels and the role of profitability in solvency for Sharia life insurance companies in Indonesia from 2015 to 2020. The insufficiency of tabarru’ funds can result in the inability of Sharia life insurance companies to pay benefits or claims, leading to a solvency level falling below the regulatory requirement of 120%. Qardh serves as a method to maintain the adequacy of tabarru’ funds and solvency levels. The research employs a descriptive analysis method with purposive sampling, specifically targeting Sharia life insurance units with average assets below 7 trillion IDR. A total of 12 companies were selected as samples, and data collection was conducted through secondary documentation and literature review. The data analysis method utilized is panel data regression with a Fixed Effect (FE) approach, including classical assumption tests and hypothesis testing. The results indicate that larger tabarru’ funds reduce the need for qardh to achieve the required solvency level, while higher profitability enhances solvency. This research is expected to provide valuable insights and information for various stakeholders. It supports the development of policies and strategies to maintain solvency. For the insurance community, this study offers additional information to reinforce practices in accordance with Sharia principles, particularly concerning the financial health of Sharia life insurance, the insufficiency of tabarru’ funds, and the role of qardh in maintaining solvency.